'Twin Deficits' Hypothesis: An Assessment of Relationship and Transmission Mechanism in India. (February 2017) - M.R., Anantha Ramu
Higher and persistent level of fiscal deficit and current account deficit is the problem of the day for Indian economy. There exists an argument that higher fiscal deficit is the major factor behind worsening balance of payments position. However, there is no identical perception on the relationship between fiscal deficit and current account deficit both theoretically and empirically. Hence this article is a revisit to the existing debate to see whether fiscal deficit and current account deficit can be called as 'twin deficits' pertaining mainly to Indian economy. Using long-term annual data for the period 1980–1981 to 2012–2013 on Indian economy and using vector error correction method, this article seeks to prove that there exists long-term positive association between fiscal deficit and current account deficit, and hence can be called as 'twins'. Using structural VAR method it has been proved here that fiscal deficit is in line with the pattern illustrated in Keynesian absorption theory and Mundell–Fleming model in regard to its impact on current account deficit. This article negates the relevance of Ricardian equivalence theory in Indian context.